Shrinking Cities of the Russian Arctic: Public Discourse of Vorkuta Residents on the Place Identity and the Reasons for Population Outflow - Elena V. Nedoseka; Ekaterina N. Sharova; Veronika A. Lisova (Арктика и Север)
The aim of the article is to identify the most significant causes of population decline in the regions of the Russian Arctic. The object of this study is the urban communities of Vorkuta, represented in social networks. The concept of the declining city, which has received various interpretations both in foreign and domestic scientific literature, and the concept of place identity have been chosen as the theoretical framework for comprehending the problem. The paper presents theoretical approaches to the definition of a shrinking city and provides a justification for the use of the concept of place identity. Shrinking cities are understood as the cumulative result of economic and demographic factors that cause population decline in the form of natural decline and migration outflow. The methodological basis of the work was the method of qualitative text analysis. The narrative analysis method was chosen as the main method of analyzing qualitative data. At the empirical level, a more detailed analysis of the subjective perception of the urban environment and the reasons for the population outflow from Vorkuta, reflected in the public discourse of the participants of the city’s online community in the VKontakte social network, was carried out. The initial analysis base included community posts and comments for 2022 (a total of 9032 posts and 191733 comments), the target sample was 64 posts and 366 comments to them. Using open and axial coding techniques, the dominant subdiscourses in the perception of place identity and a group of urban development problems that cause the outflow of population from the city were meaningfully identified. Quantitative analysis of the number of comments (under posts) and likes (under comments) made it possible to identify the most significant and persistent problems, which are certainly of increased interest to representatives of municipal and regional authorities.